Legal Protection For Surgeons In The Context Of Informed Consent For Digestive Surgical Procedures At The Banten Regional General Hospital - Adi Rastono; Ferry Fathurokhman; Ikomatussuniah Ikomatussuniah (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
The background of this research is based on the fact that all medical procedures performed by healthcare professionals require prior consent from the patient. The patient must be fully informed and understand all aspects of the medical procedure. The importance of the equal legal relationship between doctors and patients necessitates knowledge of the protection of their practices and actions to prevent unilateral harm. Therefore, informed consent serves as an instrument of legal protection for doctors, and its forms and implementation are explored. This research employed a normative-empirical juridical method with a qualitative approach, combining literature studies and field data in the form of questionnaires for surgeons. The results showed that although 75% of doctors understood the importance of informed consent as part of professional ethics and legal protection, challenges persisted in its implementation, such as time constraints, lack of patient understanding, and suboptimal internal hospital oversight. Furthermore, it was found that approximately 10% of surgical procedures experienced discrepancies between the initial plan and the final outcome, necessitating re-informed consent to maintain transparency and avoid legal action. This study demonstrates that legal protection for doctors and the implementation of informed consent have been implemented in accordance with applicable legal and ethical standards. However, the researchers also recommend regular and systematic outreach to medical personnel, improvements in documentation and oversight of informed consent implementation in hospitals, and recommendations for re-informed consent if there is a discrepancy between the procedures implemented in all hospitals and regulations.